The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.taap.2011.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent genotoxic mechanisms of monomethylarsonous acid: Role of ROS-induced DNA damage and poly(ADP-ribose) polymerase-1 inhibition in the malignant transformation of urothelial cells

Abstract: Exposure of human bladder urothelial cells (UROtsa) to 50 nM of the arsenic metabolite, monomethylarsonous acid (MMAIII), for 12 weeks results in irreversible malignant transformation. The ability of continuous, low-level MMAIII exposure to cause an increase in genotoxic potential by inhibiting repair processes necessary to maintain genomic stability is unknown. Following genomic insult within cellular systems poly(ADP-ribose) polymerase-1 (PARP-1), a zinc finger protein, is rapidly activated and recruited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Although an elevation in DNA damage has been detected in UROtsa between one and three months of exposure to MMA(III) and attributed to elevation in ROS (Wnek et al, 2009, 2010, 2011), oxidative stress did not appear as a significant category in the Gene Ontology analysis of the first two months of exposure. It is certain that an increasing trend was observed with endogenous ROS, but only a significant change was measured at three months of exposure.…”
Section: Discussionmentioning
confidence: 87%
“…Although an elevation in DNA damage has been detected in UROtsa between one and three months of exposure to MMA(III) and attributed to elevation in ROS (Wnek et al, 2009, 2010, 2011), oxidative stress did not appear as a significant category in the Gene Ontology analysis of the first two months of exposure. It is certain that an increasing trend was observed with endogenous ROS, but only a significant change was measured at three months of exposure.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, generation of ODD is often times reliable evidence of oxidative stress in malignantly transformed cells (Kryston et al 2011). In this regard, ROS-generated oxidative stress and mutation is believed to be to be an important mechanism in arsenic-induced cancers (Valko et al, 2006; Kitchin and Conolly, 2010) as exposure to arsenicals induces ODD in various cells (Nesnow et al, 2002; Gomez et al, 2006; Kojima et al 2009; Wnek et al, 2011). In the current study, MMA III caused a remarkably similar temporal pattern of ODD generation in both the methylation-deficient cells and methylation-proficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…ROS generated during arsenic exposure or arsenic metabolism is suspected to play a role in arsenic-induced carcinogenesis (Valko et al, 2006; Kitchin and Conolly, 2010), although this has not been directly shown in tumor end-point studies. However, studies have shown exposure to iAs or MMA III will induce ODD as a result of ROS generation (Nesnow et al, 2002; Gomez et al, 2006; Kojima et al, 2009; Wnek et al, 2011). At least in some cells, this has been shown to be related to oncogenic transformation, as a blockade of arsenical-induced ODD effectively blocks acquisition of cancer phenotype (Kojima et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the IARC review, chronic exposures to iAs in drinking water have been linked to an increased risk of skin, bladder, lung and possibly liver cancer. DNA damage by reactive oxygen species generated in response to iAs exposure and inhibition of DNA repair mechanisms by iAs or its metabolites have been suggested as potential mechanisms underlying the carcinogenic effects of iAs (Kligerman et al 2010; Wnek et al 2011). iAs and its trivalent methylated metabolites, MAs III and DMAs III , are also potent endocrine disruptors that affect several pathways and mechanisms regulating hormone production or function, including glucose stimulated insulin secretion by pancreas (Díaz-Villaseñor et al 2006; Douillet et al, 2013; Fu et al 2010) or insulin signaling and insulin-dependent glucose uptake in adipocytes (Walton et al 2004; Paul et al 2007a).…”
Section: Introductionmentioning
confidence: 99%